Preliminary analysis of cryopreservation of Dendrobium Bobby Messina orchid using an encapsulation-dehydration technique with Evans blue assay - Zainuddin, Masitah; Julkifle, Advina Lizah; Pobathy, Ranjetta; Sinniah, Uma Rani; Khoddamzadeh, Amir; James Antony, Jessica Jeyanthi; Pavallekoodi,; Subramaniam, Sreeramanan (Academic Journals, 2011)
In vitro grown protocorm-like bodies (PLBs) of Dendrobium Bobby Messina hybrid were cryopreserved in liquid nitrogen (LN) at -196°C by an encapsulation-dehydration technique. PLBs (1 to 2 and 3 to 4 mm) were precultured in half strength semi-solid MS media supplemented with six different concentrations of sucrose (0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 M). The PLBs were then encapsulated to form the beads in halfstrength liquid MS media supplemented with different concentrations of sodium alginate (2.5, 3.0 and 3.5%). The beads were placed in 2 ml cryovials and plunged into LN for 24 h. The beads were then thawed in a 40°C water bath for 90 s and were placed in recovery media composed of half strength semisolid MS media supplemented with 2% sucrose for four days under dark condition. After 12 days, the Evans blue dye assay was carried out to determine the viability of the PLBs. The highest viability was found in 1 to 2mm PLBs precultured in half strength semi-solid MS media supplemented with 1.0 M sucrose and encapsulated in 2.5% sodium alginate. Biochemical content analyses (chlorophyll, total soluble protein and peroxidase activities) were done to investigate the physiological responses of the PLBs after cryopreservation.